(untitled) (TRAKIA JOURNAL OF SCIENCES, 2025)
Investments are an important part of the development of municipalities and Stara Zagora region is no exception. With its very strategic location and significant trade and investment flows in recent years, the region is characterized by a diverse economy, in which the energy sector, agriculture and industry play an important role. The purpose of this article is to examine and analyse key indicators for the region and to derive the main prospects for attracting investments. Methods, such as comparative analysis, mathematical approach, deduction and induction are used. The main trends in the field of investments are touched upon - nearshoring and friendshoring. The conclusions reach specific proposals for improving the investment climate in Stara Zagora region, which will lead to economic growth and higher living standards for the citizens.